The Impact of Monetary Policy and International Trade on Economic Growth and Inflation in ASEAN-4 Countries - Rini Dwi Astuti; Didit Welly Udjianto (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Economic growth and price stability are the main goals of macroeconomics, among other goals. The central bank can influence the economy to achieve the desired condition through its monetary policy. This study aims to analyze the effect of monetary policy and international trade on economic growth and inflation in four ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand), using panel data analysis and vector autoregression. The impulse response results show that monetary policy with an interest rate policy instrument hurts economic growth in the short run and is positive in the long run. In the short run, an expansionary monetary policy has effectively accelerated economic growth, vice versa. International trade positively affects economic growth in ASEAN-4 countries in the short run and vice versa in the long run. Panel data analysis shows a price puzzle regarding the effect of interest rates on inflation. Likewise, the effect of international trade on inflation shows a positive influence. An increase in exports encourages an increase in aggregate demand and prices. The implications of the results of this study are the need for policy coordination monetary policy, trade policy, and policy in the real sector so that the effectiveness of monetary policy increases.How to Cite:Astuti, R. D., & Udjianto, D. W. (2022). The Impact of Monetary Policy and International Trade on Economic Growth and Inflation in ASEAN-4 Countries. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 175-190. https://doi.org/10.15408/sjie.v11i1.22142.